EVALUATION OF FRACTURE RISK AMONG TYPE 2 DIABETES PATIENTS WITH NON-VALVULAR ATRIAL FIBRILLATION RECEIVING DIFFERENT ORAL ANTICOAGULANTS - Lui, David; Tang, Eric; Lam, Karen; Wong, Carlos (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVES Patients with type 2 diabetes are at higher fracture risk owing to the attenuated bone turnover and impaired bone microarchitecture. The comparative effect of warfarin over non-vitamin K antagonist oral anticoagulants (NOACs) on incident fractures among patients with type 2 diabeteswith atrial fibrillation (AF) remains to be elucidated. METHODOLOGY This was a retrospective propensity-score weighted population-based cohort study of adults with type 2 diabetes and AF who were started on warfarin or NOAC between 2005 and 2019, identified from the electronic database of the Hong Kong Hospital Authority. The primary outcome was a composite of major osteoporotic fractures (hip, clinical vertebral, proximal humerus and wrist). Hazard ratios (HR) were calculated using Cox proportional hazard regression models. RESULTS This study included 15,770 patients with type 2 diabetes and AF (9,288 on NOAC and 6,482 on warfarin). During a median follow-up of 20 months, 551 patients (3.5%) sustained major osteoporotic fractures (201 in the NOAC group [2.2%]; 350 in the warfarin group [5.4%]). The adjusted cumulative incidence was lower among NOAC users than warfarin users (HR 0.80, 95% CI 0.64-0.99, p=0.044). Sub- group analyses showed consistent protective effects against major osteoporotic fractures among NOAC users across sex, age, HbA1c, duration of diabetes and history of severe hypoglycemia, compared with warfarin users. CONCLUSION Among patients with type 2 diabetes and AF, treatment with NOAC was associated with a lower risk of major osteoporotic fractures than warfarin. NOAC may be the preferred anticoagulant from the perspective of bone health.